The railway children [videorecording (DVD)] - Brocklehurst, Danny, 1971-; Rodgers, Jemma; Jeffries, Lionel; Agutter, Jenny; Smith, Sheridan, 1981-; Bradley, John, 1988-; Gadsdon, Beau; Nesbit, E. (Edith), 1858-1924 (Breaking Glass Pictures, 2023)
As WWII makes city life in Britain more and more dangerous, three evacuee children are sent to the English countryside to the home of Bobbie Waterbury, who knows the children will find as much adventure along the railway as she had years before. No one could possibly know how dangerous that adventure would grow after they discover an injured US soldier hiding instide the station.